Adverse reactions of Methylphenidate in children with attention deficit-hyperactivity disorder: Report from a referral center - Zahra Khajehpiri; Javad Mahmoudi-Gharaei; Toktam Faghihi; Iman Karimzadeh; Hossein Khalili; Mostafa Mohammadi (Wolters Kluwer Medknow Publications, 2014)
Objective: The aim of the current study was to determine various aspects of methylphenidate adverse reactions in children with attention deficit-hyperactivity disorder (ADHD) in Iran. Methods: During the 6 months period, all children under methylphenidate treatment alone or along with other agents attending a university-affiliated psychology clinic were screened regarding all subjective and objective adverse drug reactions (ADRs) of methylphenidate. Causality and seriousness of detected ADRs were assessed by relevant World Health Organization definitions. The Schumock and Thornton questionnaire was used to determine preventability of ADRs. Findings: Seventy-one patients including 25 girls and 46 boys with ADHD under methylphenidate treatment were enrolled within the study period. All (100%) ADHD children under methylphenidate treatment developed at least one ADR. Anorexia (74.3%), irritability (57.1%), and insomnia (47.2%) were the most frequent methylphenidate-related adverse reactions. Except for one, all other detected ADRs were determined to be mild. In addition, no ADR was considered to be preventable and serious. Conclusion: Our data suggested that although methylphenidate related adverse reactions were common in children with ADHD, but they were mainly mild and nonserious.